2014
DOI: 10.2332/allergolint.13-oa-0661
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Habits and Prevalence of Allergic Rhinitis in 6 to 7-Year-Old Schoolchildren in Turkey

Abstract: Frequent consumption of cereals, rice, pasta and chocolates may have beneficial effect on symptoms of rhinoconjunctivitis. Although dietary habits may affect the prevalence of symptoms of current rhinoconjunctivitis, the Mediterranean diet alone may not be protective against rhinoconjunctivitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
1
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(94 citation statements)
references
References 28 publications
4
70
1
16
Order By: Relevance
“…[5] Türkiye'de 6-7 yaş grubundaki genel sıklık değişik çalışmalarda %2.9-43.5 arasında bildirilmiştir. [6,7] ark. [6][7][8] tarafından İstanbul'da yapılan çalışma-da 6-7 yaş grubu çocuklarda hekim tanılı AR prevalansının ortalama %8.1 (%5.4-12.5) olduğu, İstanbul'un Avrupa yakasında (Eminönü, Güngören) Anadolu yakasından (Adalar) daha yüksek oranda olduğu ve İstanbul'un değişik ilçelerinde iki kata kadar fark bulunduğu bildirilmiştir.…”
Section: Tanımunclassified
See 2 more Smart Citations
“…[5] Türkiye'de 6-7 yaş grubundaki genel sıklık değişik çalışmalarda %2.9-43.5 arasında bildirilmiştir. [6,7] ark. [6][7][8] tarafından İstanbul'da yapılan çalışma-da 6-7 yaş grubu çocuklarda hekim tanılı AR prevalansının ortalama %8.1 (%5.4-12.5) olduğu, İstanbul'un Avrupa yakasında (Eminönü, Güngören) Anadolu yakasından (Adalar) daha yüksek oranda olduğu ve İstanbul'un değişik ilçelerinde iki kata kadar fark bulunduğu bildirilmiştir.…”
Section: Tanımunclassified
“…Örneğin; respiratuar sinsityal virüs bronşioliti, pnömoni, boğmaca ve kızamığa bağlı ASYE gibi enfeksiyonlar riski artırabilir. [6,60] Alt solunum yolu enfeksiyonu dışında tekrarlayan viral enfeksiyonlar immatür immün sistemi T helper 1 (Th1) yönüne kaydırmakta ve alerjik hastalık riskini azaltıcı etki yapmaktadır. Benzer şekilde mikrobiyal maruziyetin yoğun olduğu durumlar da (evdeki büyük kardeşlerin varlığı, kreşe devam etme, orofekal yolla bulaşan enfeksiyon geçirme, yedi yaş öncesinde çiftlik hayvanları ile düzenli temas) immatür immün sistemi Th1 yönüne kaydırmaktadır.…”
Section: çOcukluk çAğı Enfeksiyonlarıunclassified
See 1 more Smart Citation
“…It has been reported that in Turkey, the prevalence of pediatric AR in the 6-7 and 13-14 years of age groups is 3-44% and 3-23%, respectively, in different studies. The prevalence is higher in western parts of the country and western cities (3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…In Turkey, various studies were done on the prevalence of sensitivity to allergens in AR patients, but there has not been any reported study on the children of Sakarya, a developed province of the Marmara region in Western Turkey (3)(4)(5)(6)(7). The purpose of this study was to find out the sensitization rates to prominent inhalant and food allergens causing AR symptoms for which pediatric patients were referred to the first and only allergy outpatient clinic of Sakarya.…”
Section: Introductionmentioning
confidence: 99%